UJI BAKTERIOLOGIS BEBERAPA BUMBU PECAL KEMASAN YANG BEREDAR DI KOTA PADANG - Anggrayesti, Widya; Fifendy, Mades; Nurmiati, Nurmiati (STKIP PGRI Sumbar, 2013)
ABSTRACT Pecal is one of the culinary heritage of Indonesia are very popular. In some markets and supermarkets many outstanding flavor pecel fast food packaging is complete with herbs. The number of outstanding condiment packaging pecal feared pengkontaminan contain bacteria such as E. coli and Coliform that comes from the ingredients and mixing water and Process are not hyegienic that will impact health eating. This study aimed to test the bacteriological content of spice packaging pecal circulating in the city of Padang. This study was conducted in July-August 2013 in the laboratory of Microbiology, State University of Andalas Padang. The method used was a descriptive survey. The samples tested were some seasoning pecal packaging consisting of 5 different brands with the brand code G , S , B , C , and R. Testing is done is to calculate the total number of bacteria ( ALT ) and see the amount of gas positive tubes using tables MPN ( Most Probable Number ) by the series 5-1-1. Three types of tests performed is the test estimation, test and test complementary assertion. The results showed that of the 5 brands tested, namely G , S , B , C , and R positive for coliform , and brand G , B , C , and R are E. coli and S brand just is not there E.coli. Total plate count test showed that the highest number was found on total bacterial brand of R with 49x 106 cfu/g. In accordance with the Decree of the Minister of Health Nomor1098 / Minister / SK / VII/89 on the Limits of Microbial Contamination in Food, number of bacteria E. Required coli cells per gram of sample 0 food and 0 cells per 100 ml of sample drinks as well as total plate count (total bacteria) by the Indonesian BPOM about the type and maximum limit microbial contamination in food HK.00.06.1.52.40011 numbers in 2009 for the number of bacteria colonies / gram sample is 1x104 cfu / g.